UNVEILING PATRIARCHAL STRUCTURES AND FEMALE DEFIANCE IN DIAN PURNOMO`S PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM: A FEMINIST ANALYSIS - Fikni, Zahratul; Husnu, Muhammad; Nurjaningsih, Fiyola; Wati, Laila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article investigates the intricate dynamics of systemic patriarchy and women’s resistance as portrayed in Dian Purnomo’s novel, Perempuan yang Menangis Kepada Bulan Hitam. Utilizing Sylvia Walby’s structural theory of patriarchy alongside bell hooks’ feminist perspectives on resistance, the study examines how the protagonist navigates the deeply oppressive cultural tradition of kawin tangkap (bride capture) in Sumba. Adopting a qualitative descriptive methodology, the research analyzes textual data to uncover the underlying mechanisms of male domination and female agency. The findings demonstrate that patriarchal control is systematically enforced through the cultural normalization of subjugation, multi-dimensional gender-based violence, and the institutionalization of forced marriage. In response to this profound oppression, the protagonist exhibits a dynamic trajectory of defiance, evolving from immediate verbal and emotional rejection to strategic silence and, ultimately, open physical rebellion and formal legal confrontation. This study concludes that the novel serves not merely as a fictional narrative, but as a critical socioliterary document that exposes tradition-based violence while emphatically championing women’s inherent capacity to challenge and dismantle entrenched patriarchal frameworks.